Arginine-vasopressin infusion in a child with cranial diabetes insipidus during hyperhydration therapy with chemotherapy: a therapeutic challenge. (17th February 2021) - Devaraja, Janani; Sloan, Sarah; Lee, Vicki; Dimitri, Paul
Abstract : Summary: An 11-year-old girl presented with acute lower limb weakness, dehydration, hypernatraemia and secondary rhabdomyolysis on a background of an 8-month history of polyuria. Radiological investigations revealed a suprasellar tumour which was diagnosed on biopsy as a non-metastatic germinoma. Further endocrinological investigations confirmed panhypopituitarism and she commenced desmopressin, hydrocortisone and thyroxine. Her chemotherapeutic regime consisted of etoposide, carboplatin and ifosfamide, the latter of which required 4 litres of hyperhydration therapy daily. During the first course of ifosfamide, titration of oral desmopressin was trialled but this resulted in erratic sodium control leading to disorientation. Based on limited literature, we then trialled an arginine-vasopressin (AVP) infusion. A sliding scale was developed to adjust the AVP dose, with an aim to achieve a urine output of 3–4 mL/kg/h. During the second course of ifosamide, AVP infusion was commenced at the outset and tighter control of urine output and sodium levels was achieved. In conclusion, we found that an AVP infusion during hyperhydration therapy was required to achieve eunatraemia in a patient with cranial diabetes insipidus. Developing an AVP sliding scale requires individual variation; further reports/case series are required to underpin practice. Learning points: Certain chemotherapeutic regimens require large fluid volumes of hyperhydration therapy which can result in significant complications secondary to rapid serum sodium shifts in patients with diabetes insipidus. The use of a continuous AVP infusion and titrating with a sliding scale is more effective than oral desmopressin in regulating plasma sodium and fluid balance during hyperhydration therapy. No adverse effects were found in our patient using a continuous AVP infusion. Adjustment of the AVP infusion rate depends on urine output, fluid balance, plasma sodium levels and sensitivity/response of the child to titrated AVP doses.